Characteristics of Individuals Who Chose to Participate in a Preceptor Continuing Professional Development Program - Shweta Shah; Raymond Chojnacki; Jodi Meyer; Amanda Margolis (MDPI AG, 2020)
An online program for pharmacy preceptors to improve their clinical teaching using continuing professional development (CPD) was launched in 2017. While 491 preceptors participated in the CPD program, only 35% of potential participants completed this voluntary program. A secondary data analysis was undertaken to determine the characteristics of preceptors who completed the program and identify ways to target program advertising for those who did not complete it. Residency-trained preceptors were more likely to complete the CPD program compared with those without residency training (45% and 37%, respectively; p = 0.011). This may be due to the inclusion of CPD in residency accreditation standards. To improve completion of the CPD program by preceptors without residencies, a brief introduction to CPD, a statement of benefits, and use of a personalized plan should be included in advertisements. Preceptors teaching more experiential students were more likely to complete the CPD program (p < 0.001 for introductory and advanced experiences). To encourage preceptors with less students to participate, the CPD program should be advertised year-round to allow preceptors to complete the training when it is most relevant to their precepting schedule. Future directions include the monitoring of changes in CPD program participation rates following changes in advertisements and exploring other motivations for program completion such as collaborations with employers.